Mettl3-mediated m6A RNA methylation regulates the fate of bone marrow mesenchymal stem cells and osteoporosis. Issue 1 (December 2018) - Wu, Yunshu; Xie, Liang; Wang, Mengyuan; Xiong, Qiuchan; Guo, Yuchen; Liang, Yu; Li, Jing; Sheng, Rui; Deng, Peng; Wang, Yuan; Zheng, Rixin; Jiang, Yizhou; et al.
Abstract N6 -methyladenosine (m6 A) is the most abundant epigenetic modification in eukaryotic mRNAs and is essential for multiple RNA processing events during mammalian development and disease control. Here we show that conditional knockout of the m6 A methyltransferaseMettl3 in bone marrow mesenchymal stem cells (MSCs) induces pathological features of osteoporosis in mice.Mettl3 loss-of-function results in impaired bone formation, incompetent osteogenic differentiation potential and increased marrow adiposity. Moreover, Mettl3 overexpression in MSCs protects the mice from estrogen deficiency-induced osteoporosis. Mechanistically, we identify PTH (parathyroid hormone)/Pth1r (parathyroid hormone receptor-1) signaling axis as an important downstream pathway for m6 A regulation in MSCs. Knockout ofMettl3 reduces the translation efficiency of MSCs lineage allocator Pth1r, and disrupts the PTH-induced osteogenic and adipogenic responses in vivo. Our results demonstrate the pathological outcomes of m6 A mis-regulation in MSCs and unveil novel epitranscriptomic mechanism in skeletal health and diseases. mRNA modifications have been shown to regulate mammalian development and disease. Here the authors show that the m6 A methyltransferase Mettl3 ensures translational efficiency of the mesenchymal stem cell lineage allocator Pth1r, promoting osteogenesis and protecting from osteoporosis.